Reorientasi Jihâd Fî Sabîlillah; Menimbang Kebodohan dan Kemiskinan Sebagai Musuh Bersama - Moch. Nurcholis (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
Meaning of jihâd has been more often equated with a form of terrorism and even lead to kriminilisme. Worse, the label with negative image led to the emergence of a negative stigma against the teachings of the religion of Islam in general. As a result, there is excessive negative treatment against Islamic faiths in the discourse of international relations, both in terms of state or individual. Therefore, the mediation of the diverse teachings of jihâd in proportion the original is considered very urgent. However, the most important at this time is redefined jihâd orientation concentrate on winning against ignorance and poverty eradication and is no longer in physical victory.